Comparison of optimization based inverse simulation methods for helicopter maneuvers - Tosun, F.; Kalkan, U. (My University, 2022)
In a helicopter certification process, aviation safety agencies want to be sure that the helicopter can safely fly all maneuvers defined in its usage spectrum. Therefore, loads engineers carry out all these maneuvers for each appropriate combination of weight and center of gravity. Moreover, this maneuvering and load analysis process should be performed in the most efficient way. For this reason, this article works on two different algorithms, the gradient-based Symmetric Rank-One (SR1) and commercial optimization tool Siemens HEEDS, to perform desired helicopter maneuvers. In this study, helicopter pushover maneuver is carried out and the results for each algorithm are compared as an example. However, different maneuver results are also added to show applicability of the solution algorithms. Furthermore, rotorcraft simulation and modelling software FLIGHTLAB is used to simulate the maneuver. Rotorcraft is modeled as rigid and uniform inflow is used for the calculation of rotor aerodynamic loads.